The North African sawfly genus Prionomeion (Hymenoptera, Diprionidae), with a key to the Palaearctic genera of the subfamily Diprioninae - Hara, Hideho (Zootaxa, 2016)
The diagnostic characters are discussed for the North African genus Prionomeion Benson, 1939 (Hymenoptera, Diprionidae, Diprioninae). The type species, Prionomeion gaullei (Konow, 1906), is redescribed based on the holotype (female) and one male, both from Algeria. The second species of the genus, P. maghrebense sp. nov. is described based on one female from Morocco and one male from Algeria. A key to the Palaearctic genera of the subfamily Diprioninae is given.